2013
DOI: 10.1016/j.ejca.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor loss in endometrial carcinoma curettage predicts lymph node metastasis and poor outcome in prospective multicentre trial

Abstract: Double negative hormone receptor status in endometrial cancer curettage independently predicts lymph node metastasis and poor prognosis in a prospective multicentre setting. Implementing hormone receptor status to improve risk-stratification for selecting patients unlikely to benefit from lymphadenectomy seems justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
145
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(155 citation statements)
references
References 37 publications
9
145
1
Order By: Relevance
“…Some univariable factors, FGFR2 mutation and hormone receptor status, lost significance in multivariable analysis. This may be due to the fact that FGFR2 mutations were equally frequent in MSI and NSMP endometrial carcinomas, and that hormone receptor loss was mainly found in p53-mutant and L1CAM-positive endometrial carcinomas but was also frequently observed in POLE-mutant endometrial carcinomas (10,(26)(27)(28). MSI, p53, and L1CAM proved stronger independent prognosticators in this analysis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Some univariable factors, FGFR2 mutation and hormone receptor status, lost significance in multivariable analysis. This may be due to the fact that FGFR2 mutations were equally frequent in MSI and NSMP endometrial carcinomas, and that hormone receptor loss was mainly found in p53-mutant and L1CAM-positive endometrial carcinomas but was also frequently observed in POLE-mutant endometrial carcinomas (10,(26)(27)(28). MSI, p53, and L1CAM proved stronger independent prognosticators in this analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Several molecular alterations, such as hormone receptor expression, CTNNB1 and FGFR2 mutations, have been previously reported as having prognostic potential in single biomarker studies (8,9,13,19,22,26,27). Some univariable factors, FGFR2 mutation and hormone receptor status, lost significance in multivariable analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Other approaches have been conducted to try to estimate LN metastatic risk 57 . For example, double negative hormone receptor status in EC curettage has recently been suggested to independently predict LN metastasis 57 .…”
Section: Groups Risk Based On Biomarkers To Predict Ln Metastatic Promentioning
confidence: 99%
“…For example, double negative hormone receptor status in EC curettage has recently been suggested to independently predict LN metastasis 57 . In Trovik et al study, 26% of patients with combined loss of estrogen-and progesterone receptors expression had LN metastasis.…”
Section: Groups Risk Based On Biomarkers To Predict Ln Metastatic Promentioning
confidence: 99%
“…Most of the current molecular signatures under consideration perform the first step but not the second; that is, they contain a set of key biomarkers, but do not apply a systematic method for predicting the outcome on an independent testing cohort. For example, absence of expression of the estrogen receptor (ER) and progesterone receptor (PR) genes, the so-called double-negative situation, correlates with increased risk of lymph node metastasis [7]. However, this correlation does not appear to translate into a prognostic test that can predict lymph node metastasis on a patientby-patient basis.…”
mentioning
confidence: 99%